AI WRITING CORRECTION TOOLS: TEACHERS AND STUDENTS’ PERCEPTION - Putra, Mulyono (Jurnal Tatsqif, 2023)
This study investigates the similarities and differences of perceptions of teachers and students, examines the issue of academic integrity, and explores the potential for incorporating AI writing correction tools into language teaching and learning. Eighteen lecturers and thirty-nine graduate students were asked to respond to a closed- and open-ended questionnaire to answer the research questions. The sample was collected from the TESOL program at St. Andrews University's International Education Institute. The questionnaire was analysed using Qualtrix to see the patterns from the Likert scale, and thematic analysis was utilized to anticipate the identified themes from the open-ended questionnaire. The findings show that teachers and students have various opinions about using AI writing correction tools in a classroom setting, with some similarities and differences. Interestingly, the majority of teachers and students did not regard the use of AI writing correction tools as a violation of academic integrity. Furthermore, there was a conflicting view among teachers about integrating AI writing correction tools in the classroom. Meanwhile, most students agreed that AI writing could be integrated into teaching and learning.